Kurs, Nilai Ekspor, dan Cadangan Devisa di Indonesia (Tinjauan Empiris Tahun 2013 - 2022) - Maghfiroh, Laila; Anggraeni (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
Foreign exchange reserves are the total amount of foreign currency owned by a country. A country's economy can be said to be strong or weak based on the level of foreign exchange reserves owned by that country. The aim of this research is to partially and simultaneously analyze the influence of the exchange rate, export value, import value and inflation on foreign exchange reserves in Indonesia. This research was processed using the SPSS version 25 program using multiple linear regression analysis. This research data was collected through observation and documentation of existing data at the Central Statistics Agency (BPS) and Bank Indonesia (BI). The results of this research show that: First, partially the exchange rate and export value have a significant positive effect on foreign exchange reserves in Indonesia, the value of imports has an insignificant positive effect on foreign exchange reserves in Indonesia, and inflation has a significant negative effect on foreign exchange reserves in Indonesia. Second, simultaneously the exchange rate, export value, import value and inflation have a significant effect on foreign exchange reserves in Indonesia. Keywords: Foreign Exchange Reserves, Exchange Rates, Export Values, Import Values, and Inflation